2009
DOI: 10.1016/j.aquaculture.2009.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an herbivorous diet on energy balance of Litopenaeus vannamei at selected ontogenetic stages

Abstract: Herbivorous (20% vegetable protein, 40% carbohydrate) and carnivorous diets (40% marine animal protein, 20% carbohydrate) were experimentally tested to assess their effect on the energy balance and energetic substrates utilized by postlarvae (PL's /15 days) and juvenile shrimp (3-6 g) of Litopenaeus vannamei. Postlarval stage 60 (PL 60 , early juveniles) shrimps fed HeD and CaD diets, then late juveniles (3-6 g) acclimated to the same diets were tested for their respective energy partitioning potential. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…Energy budget in shrimp may be influenced by different factors such as temperature (Su et al, 2010;Wang et al, 2006;Yan et al, 2007), salinity (Rosas et al, 2002;Su et al, 2010;Yan et al, 2007;Ye et al, 2009), life stage (Lemos and Phan, 2001;Maldonado et al, 2009), and nutritional composition of food (Jiménez-Yan et al, 2006;Rosas et al, 2001;Suárez et al, 2009;Wang et al, 2006). The present study observed the influence of different dietary food sources in absolute (kJ g -1 ) and relative (%) terms of the variables of the bioenergetics equation (C=P+R+U+F+E) for juvenile L. vannamei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy budget in shrimp may be influenced by different factors such as temperature (Su et al, 2010;Wang et al, 2006;Yan et al, 2007), salinity (Rosas et al, 2002;Su et al, 2010;Yan et al, 2007;Ye et al, 2009), life stage (Lemos and Phan, 2001;Maldonado et al, 2009), and nutritional composition of food (Jiménez-Yan et al, 2006;Rosas et al, 2001;Suárez et al, 2009;Wang et al, 2006). The present study observed the influence of different dietary food sources in absolute (kJ g -1 ) and relative (%) terms of the variables of the bioenergetics equation (C=P+R+U+F+E) for juvenile L. vannamei.…”
Section: Discussionmentioning
confidence: 99%
“…The energy acquired via food intake is channeled between the vital process of activities of growth, metabolism, ammonia excretion, feces, and, in the case of shrimp, molting (Jobling, 1993;Lemos and Phan, 2001;Petrusewicz and Macfadyen, 1970). The partitioning of the ingested energy between these processes may depend on variables such as shrimp life stage (Lemos and Phan, 2001;Maldonado et al, 2009), dietary composition (Gauquelin et al, 2007;Jiménez-Yan et al, 2006;Suárez et al, 2009;Wang et al, 2006), and environmental factors (Rosas et al, 2001;Su et al, 2010;Wang et al, 2006;Yan et al, 2007;Ye et al, 2009). The ratio of energy partitioned between growth and other metabolic processes may represent the efficiency of energy utilization (Duncan and Klekowski, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HeE was higher than RE in CW shrimp whereas the reverse was true in BFT shrimp; shrimp fed only with commercial shrimp feed could not satisfy all their nutritional requirements (Rosas 2003). The higher HiE in CW than in BFT shrimp indicates that more energy is necessary to absorb and assimilate the food and could be an effect of the protein origin (Rosas 2003;Maldonado et al 2009). The higher growth of BFT shrimp corresponds to an energy loss as E v higher than in CW shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…The energy balance was derived from the following equation (Cho and Bureau 1998;Maldonado et al 2009):…”
Section: Energy Balancementioning
confidence: 99%
“…Our research group developed a program of experiments on shrimp nutrition that successfully tested plant meal such as plant protein concentrates as fishmeal substitutes (Maldonado, Cuzon, Guzmán, Brito, Soto, Arena, & Gaxiola, 2009;Suárez, Gaxiola, Mendoza, Cadavid, Garcia, Alanis, Suárez, Faillace, & Cuzon, 2009;Maldonado, Guillen, Pantoja, Arena, Ezquerra-Bauer, Alvarez-González, Cuzon, & Gaxiola, 2012;Suarez, Gaxiola, Posso, Garcia, Alanis, Suárez, Faillace, & Cuzon, 2012). However, plant protein sources have limitations related to decreased feed intake due to lack of appetability for shrimp, and by the presence of phytate, an antinutritional factor (AF), which limits bioavailability of phosphorus and other minerals (Lee and Meyers, 1996;Mendoza, Aguilera, & Montemayor, 2000).…”
Section: Introductionmentioning
confidence: 99%